Novel MSH6 exon 5–6 skipping variant in a Taiwanese family with Lynch syndrome: implications for genetic testing and cancer management - Ting-Yao Wang; Chao-Yu Chen; Huei-Chieh Chuang; Yuan-Yuan Jiang; Jrhau Lung (Molecular Cytogenetics)
Abstract Lynch syndrome is an autosomal dominant disorder predisposing individuals to colorectal and other cancers, primarily caused by variants in mismatch repair genes. This study describes a novel MSH6 variant affecting transcript structure in a Taiwanese family meeting the Amsterdam II criteria for Lynch syndrome. A 67-year-old male presented with jejunal adenocarcinoma and a strong family history of colorectal cancer. Immunohistochemistry revealed loss of MSH6 expression, while next-generation sequencing performed on tumor tissue failed to detect any MSH6 variants. Comprehensive genetic analysis, including RT-PCR and Sanger sequencing of both cDNA and genomic DNA, identified a novel exon 5–6 skipping variant in the MSH6 gene transcript (NM_000179.3:r.3262_3645del), linked to a 2268 bp deletion from the 3’ portion of intron 4 to the middle of intron 6 of the MSH6 gene (NC_000002.12:g.47803007_47805274del). This variant was also detected in two of the patient’s asymptomatic sons, highlighting its heritability and potential cancer predisposition. The study emphasizes the limitations of capture-enrichment NGS panels in detecting certain types of variants and underscores the value of orthogonal confirmation using cDNA analysis for transcript aberrations. The identification of this novel variant expands our understanding of Lynch syndrome’s mutational spectrum and has implications for genetic diagnosis and counseling. Based on these findings, the patient was treated with pembrolizumab, resulting in stable disease for 8 months. This case highlights the importance of comprehensive genetic approaches in suspected Lynch syndrome cases and the potential utility of mRNA-based screening as an additional method when NGS analysis is negative and the clinical presentation strongly suggests Lynch syndrome.